Analisis Pengaruh Variasi Rekonstruksi Slice Thickness Dan Rekonstruksi Increment Terhadap Informasi Citra Anatomi Pemeriksaan MSCT Scan Sinus Paranasal Potongan Coronal Pada Kasus Rhinosinusitis Kronis Di RSUP Prof. Dr. I.G.N.G Ngoerah - Gabrila Febyolla Pajeko; Anak Agung Aris Diartama; I Made Purwa Darmita (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: One of the modalities used to diagnose chronic rhinosinusitis is MSCT Scan. In MSCT Scan, there are several scanning parameters used, namely slice thickness and reconstruction increment. This study aims to determine the effect of variations in slice thickness reconstruction and increment reconstruction on the anatomical image information of MSCT scans of coronal paranasal sinuses in cases of chronic rhinosinusitis. Method: This type of research is quantitative research with an experimental approach carried out at the radiology installation of Prof. RSUP. Dr. I.G.N.G Ngoerah in June-July 2023. This study used 10 samples and each radiograph was reconstructed with 6 variations of slice thickness reconstruction and increment reconstruction. Results: Based on the results of the overall anatomical Friedman test, a p value of 0.000 was obtained (p value <0.05), which can be interpreted as Ho being rejected and Ha being accepted so that there is a difference in overall anatomical image information on the MSCT scan of the coronal paranasal sinuses with 6 variations of slice thickness and reconstruction. increment reconstruction in cases of chronic rhinosinusitis. Based on the Wilcoxon test, it also shows that each variation has a p value <0.05, which means there are differences in anatomical image information for each variation. Conclusion: Based on this research, it shows that there are differences in the anatomical image information of MSCT scans of paranasal sinus coronal sections with variations in slice thickness reconstruction and increment reconstruction in cases of chronic rhinosinusitis, and variation 2 produces the most optimal anatomical image information. Based on the Wilcoxon test, it also shows that each variation has different anatomical image information.